Commodification Of Social Capital In Youth Entrepreneurship : A Critical Review Of Literature - Ahamat, Amiruddin; Pillai, Tharuma Rajan (İstanbul Aydın University, 2019)
There is a clear distinction made on forms of capital accessible to young entrepreneurs,such as financial, human,physical,knowledge and social capitals.Financial, human and physical capitals are classified as tangible assets while knowledge capital is categorized as an intangible asset.Social capital suffers from ‘tomatoes syndrome’ - whether it should be considered a fruit or a vegetable,or even both – since its tangible or intangible nature is not easily ascertained.But the commodification of social capital in youth entrepreneurship as tangible, intangible or even both is the subject of much debate and academic percolation.This conceptual paper critically analyses the commodification of social capital in youth entrepreneurship and its implication on the broader development aspect of youth entrepreneurship by highlighting possible scenarios.